2021
DOI: 10.1186/s12872-021-02105-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of atrioventricular block among 15 million Chinese health examination participants in 2018: a nation-wide cross-sectional study

Abstract: Background Nationwide data on the prevalence of atrioventricular (AV) block are currently unavailable in China. Thus, we aimed to assess the prevalence and risk factors of AV block among Chinese health examination adults. Methods A total of 15,181,402 participants aged ≥ 18 years (mean age 41.5 ± 13.4 years, 53.2% men) who underwent an electrocardiogram as a part of routine health examination in 2018 were analyzed. AV block was diagnosed by physici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 32 publications
4
34
0
2
Order By: Relevance
“…Another study, in a large population of more than 15 million people, estimated a prevalence rate of 6.84%, 0.18%, and 0.04% for first-, second-and third-degree AVB respectively. They also indicated that the AVB risk was associated with older age, male sex, lower HR, higher BMI, hypertension, DM and low HDL-C (55).…”
Section: First-degree Avbmentioning
confidence: 97%
“…Another study, in a large population of more than 15 million people, estimated a prevalence rate of 6.84%, 0.18%, and 0.04% for first-, second-and third-degree AVB respectively. They also indicated that the AVB risk was associated with older age, male sex, lower HR, higher BMI, hypertension, DM and low HDL-C (55).…”
Section: First-degree Avbmentioning
confidence: 97%
“…Bradycardia or conduction blocks overall were higher in men (5.6% vs 1.9%). Shan et al described higher rates of CHB in men (0.05% vs 0.03%) in a study of 15 million people in China [ 24 ], as did Kojic et al in a prospective study of 18,912 residents of Reykjavik [ 25 ]. However there is no convincing evidence that age-dependent conduction disease requiring PPI in women is half that in men and therefore this cannot fully explain our findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent results point to a deleterious effect of low lipid levels on cardiovascular events, especially in atrial fibrillation (AF). Thus, a study on 15 million Chinese participants showed that low HDLC was independently associated with a higher risk of atrioventricular block, whereas high TC was a protective factor [ 38 ]. The protective effect of high levels of TC against AF has been demonstrated in many other studies in different populations in Korea, Japan, USA, China and Sweden [ 39 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%